Is the relation between non-controlling interests and parent companies misleading? - Lopes, A. I.; Lourenço, I.; Soliman, M. T.; Branco, M. (Australian Journal of Management, 2021)
This article investigates whether different levels of investor protection affect the equity market’s valuation of non-controlling interests (NCIs) in a consolidated corporate entity. Using a set of publicly listed European firms, our findings suggest a positive (negative) association of NCIs with parent companies’ share prices in countries with low (high) levels of investor protection. We interpret the findings as evidence that when non-controlling investors are not well-protected, parent companies have an opportunity to extract rents from non-controlling owners, leading to a positive valuation of NCIs’ equity. However, in countries where non-controlling investors are well-protected, parent companies are not able to extract rents but still must monitor and govern the related subsidiary; thus, NCIs become a net cost, and the relation inverts.